EFFECT OF SCHOOL MANAGEMENT COMMUNICATION ON ACADEMIC PERFORMANCE OF PUBLIC SECONDARY SCHOOLS IN NYATIKE SUB-COUNTY, KENYA - Nyakwama Jeria Nyarango,; Dr. Joshua Odhiambo Ogal, (IJRDO- Journal of Educational Research, 2020)
This study analyzed the strategies school managers apply to improve academic performance of students in their schools in Nyatike Sub County, Migori County, which has suffered poor school management resulting into low academic performance as stated by county education officer during education symposium in the year 2017. Validity and reliability of the study was tested. Cronchba’s Alpha Coefficient of 0.80 was confirmed the reliability of the instruments. The study was guided by the McGregor’s theory X and theory Y based on various interrelated variables such as communication, supervision, decision making and performance in schools. Population for the study comprises of 150 BOM, 120 heads of department, 120 members of parents teacher association and 33 school principals. A descriptive survey research design was adopted. Simple random sampling techniques was utilized to draw fifty members of the Board of Management (BOM), forty Heads of Department (HOD), forty members of Parents Teachers Association (PTA) and ten school principals yielding to a sample size of 140 subjects to participate in the study. A mixed method was used to collect data from respondents using questionnaire and qualitative data from heads of departments and members of PTA using interviews. Descriptive statistics which include percentages, coding, decoding of information was used in data analysis and data presentation was in tables and charts. Piloting of the research instruments was conducted. The findings of the study were used by Ministry of Education and other stake holders to improve academic performance and management of students in secondary schools. The findings of this study revealed that decision making have a great contribution in affecting the organizational objectives. So, it is vital for the school management and other stakeholders to make wise decisions in order to meet the objectives of an organization. Also this finding has found out that communication if well-made can lead to the promotion of the desired achievement of academic performance in Kenya. Also teachers and students do not work together as stakeholders which reduce the effort of academic performance to rise. The findings of this study have revealed that it is an imperative duty for the school management to promote participatory decision making system in encouraging good student performance. Consequent of these circumstances, education was not help to orient learners towards positive intellectual transformation out of which socio-economic challenges was contained. It has been evidenced that school management does not create room for all (students, teachers and community at large) to take active part in decision making on matters concerning the school prosperity.